2023
DOI: 10.1021/acsomega.3c02200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Ganoderma lucidum Proteoglycan on Type 2 Diabetic Rats and the Recovery of Rat Pancreatic Islets

Abstract: Type 2 diabetes (T2D) results from both insulin resistance and pancreatic β-cell dysfunction. A natural proteoglycan extracted from Ganoderma lucidum, namely, FYGL, has been demonstrated to be capable of ameliorating insulin resistance in previous work. In this work, a T2D rat model induced by streptozocin (STZ) and a high-fat diet was used to investigate the effects of FYGL on pancreatic functions, and the transcriptomics of the rat pancreas was used to investigate the biological processes (BP) and signal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…The animals were then given urethane anesthesia (100 mg kg −1 , intraperitoneally). 40 Blood samples were collected from a retro-orbital vein to separate the serum and the animals were then euthanized by cervical dislocation. Kidney, liver, and adipose tissue were collected from all animal groups, cleaned, and divided into several portions.…”
Section: Validation Of Molecular and Biochemical Signatures On The T2...mentioning
confidence: 99%
“…The animals were then given urethane anesthesia (100 mg kg −1 , intraperitoneally). 40 Blood samples were collected from a retro-orbital vein to separate the serum and the animals were then euthanized by cervical dislocation. Kidney, liver, and adipose tissue were collected from all animal groups, cleaned, and divided into several portions.…”
Section: Validation Of Molecular and Biochemical Signatures On The T2...mentioning
confidence: 99%
“…After the diet-induced T2D model was established, HFD/STZ rats were orally administrated FYGL or saline for 4 weeks. Basic metabolic data of SD rats have been studied and published previously, 25 as shown in Figure S7 . In this study, the tibialis anterior (TA) muscle of the rats was dissected, and the inhibitory effects of FYGL on muscle atrophy were observed by hematoxylin & eosin (H&E) staining.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Yu et al found that FYGL, a proteoglycan extracted from Ganoderma lucidum entities, could promote PPARγ expression in the pancreas of T2D rats and upregulate Pdx-1 expression to increase the number of pancreatic β-cells. Thus, FYGL was able to restore pancreatic islet function and lower blood glucose [ 72 ].…”
Section: The Primary Mechanism Of Glp In Preventing Asmentioning
confidence: 99%